Pengaruh Penggunaan Artificial Intelligence (AI), Literasi Digital, Pengalaman Pengguna terhadap Loyalitas Pelanggan pada E-commerce Shopee - Rabani, Savira Rahma; Alfadhilla, Dina Amalia; Sari, Meifa Erika; Fii Ilayana, Nantri Kusuma (Fakultas Ekonomi dan Bisnis Islam UIN Raden Mas Said Surakarta, 2024)
The increasingly sophisticated technological advances in business activities encourage Shopee e-commerce to continue to improve the quality of service in order to keep consumers loyal. This study aims to analyze the effect of artificial intelligence (AI), digital literacy, and user experience on customer loyalty in Shopee e-commerce. The method used in this study is a quantitative associative approach with data collection through a questionnaire using a Likert scale. The sampling technique applied is non-probability sampling with a purposive sampling approach using the Lemeshow formula. The results of this study reveal that there is a positive and significant influence on the use of artificial intelligence (AI) and digital literacy on customer loyalty in Shopee e-commerce. However, user experience has a negative and insignificant effect on customer loyalty in Shopee e-commerce. Therefore, good digital literacy can help Shopee e-commerce consumers understand the quality of Shopee's services that continue to increase with the use of artificial intelligence (AI) so that it can influence consumers to always be loyal to Shopee e-commerce. However, with the low consumer trust in the Shopee e-commerce user experience, consumer loyalty does not have a positive effect.